Using Teachers’ Judgments of Quality to Establish Performance Standards in Technology Education Across Schools, Communities, and Nations - Seery, Niall; Kimbell, Richard; Buckley, Jeffrey (Frontiers in Education, 2022)
The establishment and maintenance of national examination standards remains a serious issue for teachers and learners, whilst the levers of control remain firmly in the hands of Awarding Bodies and supervising politicians. Significantly, holistic assessment presents an agility and collective approach to establishing in the minds of teachers ‘what is of value’ when determining the comparative evidence of pupil performance. It is argued in this paper that the collation of the comparative judgement process can initially identify and subsequently maintain standards of performance that can be defined on a cluster, regional or even national level. Much comparative judgement research centres on the formative benefits for learners, but here we place the focus on teachers operating in collaborative groups to establish standards within and beyond their own schools, and ultimately across the nation. We model a proof-of-concept research project. A rank is produced by the collective consensus of the participating teachers and used to simulate a definition of standard. Extrapolations are statistically modelled to demonstrate the potential for this approach to establishing a robust definition of national standards. But central to the process is what is going on in the minds of teachers as they make their judgements of quality. The research aims to draw out teachers’ constructs of quality; to make them explicit; to share them across classrooms and schools; and to empower teachers to debate and agree their standards across schools. This research brings to the fore the symbiotic relationship between teaching, learning and assessment.